2014
DOI: 10.1111/mec.12691
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mitochondrial DNA and the genetic history of Eurasian beaver (Castor fiber) in Europe

Abstract: After centuries of human hunting, the Eurasian beaver Castor fiber had disappeared from most of its original range by the end of the 19th century. The surviving relict populations are characterized by both low genetic diversity and strong phylogeographical structure. However, it remains unclear whether these attributes are the result of a human-induced, late Holocene bottleneck or already existed prior to this reduction in range. To investigate genetic diversity in Eurasian beaver populations during the Holoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
(86 reference statements)
1
34
0
1
Order By: Relevance
“…A recent study of ancient mtDNA by Horn et al. () has indeed demonstrated that strong apparent phylogeographic structuring in Eurasian beaver has arisen as a result of the population bottlenecks, although they suggest that eastern and western ESUs are maintained. This analysis both examines the original samples of Durka et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of ancient mtDNA by Horn et al. () has indeed demonstrated that strong apparent phylogeographic structuring in Eurasian beaver has arisen as a result of the population bottlenecks, although they suggest that eastern and western ESUs are maintained. This analysis both examines the original samples of Durka et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Horn et al. ). Most recent common ancestor for the two clades has been estimated to be 210 000 (110 000–340 000) years old (Horn et al.…”
Section: Introductionmentioning
confidence: 98%
“…All three of the surveyed populations were genetically closely related (Horn et al, 2014). Such taxonomy is also supported by single nucleotide polymorphisms (SNPs) recently studied for autochthonous and reintroduced populations of C. fiber by Senn et al (2014).…”
Section: Discussionmentioning
confidence: 76%
“…All studied populations are genetically close and belonging to the Eastern mitochondrial haplotypes clade (Horn et al, 2014;Senn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the research has been several wild mammal, bird, reptile and fish species (e.g. Sommer et al 2009;Fraser et al 2012;Bray et al 2013;Herman et al 2014;Horn et al 2014;Nikulina, Schmölcke 2015a, 2015b, as well as domestic cattle, pigs and dogs (Nikulina, Schmölcke 2008Scheu et al 2008;Krause-Kyora et al 2013;Zhilin et al 2014;Niemi et al 2015). In particular, the genetic analysis of well-preserved teeth and bones to identify the species, the so-called DNA bar-coding, is reasonably priced and can be undertaken, for instance, in cooperation with the Centre for Baltic and Scandinavian Archaeology (ZBSA) in Schleswig, Germany, with its specialised laboratory for ancient animal DNA (Nikulina, Schmölcke 2010).…”
Section: O N C L U S I O N Smentioning
confidence: 99%